Vibration Training - Mechanisms and possible mechanisms relating to structural adaptations and acute effects - van Diemen, A. (2002)
In recent years, vibration training has received attention from science and in practice as an interesting means of achieving progress in terms of strength and speed within a short time. In addition, it has been shown that vibration training is also capable of increasing flexibility and bone density. The studies involving vibration are not unambiguous, however, which also applies to the methods used in the various studies. Where vibration frequency, amplitude and acceleration alone are concerned, practically no study is the same. The objective of this literature study is to bring clarity to the scientific results on the effects of vibration. These results are compared with current knowledge of the motor system. This method will expose the underlying mechanisms of the effects found, or the lack of these. There are still large gaps in the knowledge of the human motor system, which means that not all the mechanisms put forward in this report can avoid being hypothetical in nature. This deficiency in scientific knowledge emphasizes the importance of knowledge of vibration training gained in practice with day-to-day training. Science by no means has all the answers to questions based on practical experience and can neither confirm nor deny some practical findings. It is of major importance, therefore, to listen to the experiences of athletes and patients in rehabilitation, and to document these experiences in practice. The structure of this report is as follows. Chapter 2 provides a brief summary of present knowledge in the field of the motor system in general and spinal reflexes in particular. The latter are of particular importance in vibration training, which is presumed to have the greatest effect on this part of the motor system. Chapter 3 is a short introduction to the development of vibration training. The origins of vibration training are considered, its initial applications and recent developments. This is followed in chapter 4 by an overview of the potential of vibration training. Vibration training engages at the level of spinal reflexes and these reflexes have a great potential for increasing their efficiency. Chapter 5 is the most important section of this report. This chapter consists of an extensive review of the studies which have specifically researched the effects of vibration on force, power and flexibility, among other things. The effects on force and power are divided into acute effects and structural adaptations, because these two effects are produced by different mechanisms. Finally, chapter 6 contains a discussion of these results and their practical implications, while recommendations are also made for further research.